Strategies of linear feedback control and its classification - Saad Fawzi AL-Azzawi; Maysoon M. Aziz (Universitas Ahmad Dahlan, 2019)
This paper is concerned with the control problem for a class of nonlinear dynamical (hyperchaotic) systems based on linear feedback control strategies. Since the obtaining positive feedback coefficients are required for these strategies. From this point of view, the available ordinary/dislocated/enhancing and speed feedback control strategies can be classified into two main aspects: control the dynamical systems or can't be control although it own a positive feedback coefficients. So, we focused on these cases, and suggest a new method to recognize which system can be controller it or not. In this method, we divided the positive feedback coefficient which obtain from these strategies in to four categories according to possibility of suppression and show the reason for each case. Finally, numerical simulations are given to illustrate and verify the results.